Inside the Light Boojums: A Journey to the Land of Boundary Defects (Analysis in Theory and Applications, 2020)
We consider minimizers of the energyin a two-dimensional domain $\Omega$, with weak anchoring potentialThis functional was previously derived as a thin-film limit of the Landau-de Gennes energy, assuming weak anchoring on the boundary favoring a nematic director lying along a cone of fixed aperture, centered at the normal vector to the boundary.In the regime where $s [\alpha^2+(\pi-\alpha)^2]
Keywords: Nematics; thin-film limit; Ginzburg-Landau type energy; weak anchoring; boundary vortices; asymptotic profile.